2017
DOI: 10.5296/jee.v8i1.11338
|View full text |Cite
|
Sign up to set email alerts
|

A Historical Review of the Benefits and Hypothetical Risks of Disinfecting Drinking Water by Chlorination

Abstract: This review examines the benefits and alleged risks associated with the disinfection of drinking water by chlorination, through critical appraisal of the historical saga of chloroform as the main disinfection by-product (DBP). The author maintains that the provision of clean drinking water is a survival issue for humankind and supports unreservedly the recommendation by the World Health Organization (WHO) of the United Nations to disinfect by chlorination, for the reasons stated herein. The author aims to lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…This is mirrored by the results of others researching the health hazards of disinfection by-products. Studies show an increased risk of bladder and possibly colon cancer in people who consume chlorinated water for 35 years or more [36][37][38]. Also, Health Canada [39] report studies on humans found a link between long-term exposure to high levels of disinfection by-products, including a higher risk of developing cancer.…”
Section: Water Security As Safetymentioning
confidence: 99%
“…This is mirrored by the results of others researching the health hazards of disinfection by-products. Studies show an increased risk of bladder and possibly colon cancer in people who consume chlorinated water for 35 years or more [36][37][38]. Also, Health Canada [39] report studies on humans found a link between long-term exposure to high levels of disinfection by-products, including a higher risk of developing cancer.…”
Section: Water Security As Safetymentioning
confidence: 99%
“…These effects have been observed in a large number of people (Ayotte et al, 2017). People who consume water that have arsenic concentrations of 50 g/l or lower have been linked to an increased risk of lung and bladder cancer as well as skin changes (Cheung, 2017).…”
Section: Heavy Metals Content and Ph Values In Stream Watermentioning
confidence: 99%
“…However, these mechanisms are not efficient against cysts and oocysts of Giardia spp. and Cryptosporidium spp., since they are highly resistant (Cheung, 2017). Other Alinne Petris et al disinfection mechanisms are the use of ozone and ultraviolet (UV) radiation.…”
Section: Microbiological Analysis Of Filter Backwash Watermentioning
confidence: 99%